Enhancement of Nurse Migration and Nurse Shortages Solution among G20 Countries - Yudi Ariesta Chandra; Achir Yani Syuhaimi Hamid; Fatma Lestari; Nunung Nurhayati; Andrio Adiwibowo; Annida Falahani; Laurentia Dewi; Sri Yulia; Azimatul Aliyah; Juwi Athia Rahmini (Fakultas Keperawatan Universitas Andalas, 2026)
Nurse migration among G20 countries increased as consequence of shortage of nurses in developed country members. Concrete strategies needed to address the issues. This study aimed to propose policy recommendation to the G20 Forum to enhance nurse migration system and long-term solution for shortages of nurses. A qualitative study was conducted to collect ideas for policy recommendation through experts sharing and focus group discussion. 190 participants involved. A descriptive qualitative approach was used to analyze the data. A policy recommendation was formulated into four themes and 11 categories. The themes included (a) harmonization for equal nursing competency qualifications, (b) reinforcement of brain drain anticipation and brain gain support, (c) improvement of regulatory and data system for nurse migration, and (d) collaboration enhancement with stakeholders for an enabling environment. The formulated policy recommendation may be used as a reference for current G20 leaders to create more concrete strategies for enhancing nurse migration system and long-term solution of shortages of nurses, as part of commitment on the health agenda. Considering the finding of this study highlighted the role of NNAs and NSAs for collaboration enhancement with stakeholders for enabling environment, we suggest a further study to identify more detail strategies to enhance NNAs and NSAs’ role in enhancing registration, placement, and monitoring processes.